KESIAPAN DAN KENDALA GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN GEOGRAFI DI SMA PENGGERAK SE-KOTA PADANG - Putri, Icha Yesika; Novio, Rery (JURNAL BUANA, 2024)
The purpose of this study was to describe the readiness and constraints of teachers in implementing the Merdeka Curriculum for Geography Subjects at SMA Penggerak in Padang City. The method used in this research is descriptive quantitative. The population in this study was all SMA Penggerak in Padang City for the 2021/2022 school year. The sampling technique used was total sampling, the subjects in this study were all teachers who taught Geography class 10/phase E as many as 6 people from 5 schools. Data collection techniques used in the form of a questionnaire using a Likert scale, interviews and documentation. The results of this study indicate that there are obstacles faced by teachers in implementing the Merdeka Curriculum, including: curriculum adjustments, the absence of references in setting the flow and learning objectives and learning modules, limited time in planning, lack of teaching hours due to online or blended learning, limited facilities, and school infrastructure, lack of student activity during the learning process and student attitudes that are less concerned with assignments.